The many faces of hermes: the quality of participation experiences and political attitudes of migrant and non-migrant youth - Fernandes-Jesus, M.; Malafaia, C.; Ferreira, P.; Cicognani, E.; Menezes, I. (Human Affairs, 2012)
This paper intends to explore whether and how the quality of participation experiences is associated with political efficacy and the disposition of migrant and non-migrant young people to becoming involved. The sample includes 1010 young people of Portuguese, Angolan and Brazilian origin, aged between 15 and 29 years old. The results reveal that the quality of participation experiences is related to political efficacy and dispositions to becoming involved, but different groups seem to react differently to different forms of political action.